Aligned Cell‐Laden Yarns: Tendon Tissue Engineering: Effects of Mechanical and Biochemical Stimulation on Stem Cell Alignment on Cell‐Laden Hydrogel Yarns (Adv. Healthcare Mater. 7/2019). Issue 7 (10th April 2019) - Rinoldi, Chiara; Costantini, Marco; Kijeńska‐Gawrońska, Ewa; Testa, Stefano; Fornetti, Ersilia; Heljak, Marcin; Ćwiklińska, Monika; Buda, Robert; Baldi, Jacopo; Cannata, Stefano; Guzowski, Jan; Gargioli, Cesare; et al.
Abstract : In articule number1801218 by Wojciech Swieszkowski and co‐workers, highly aligned cell‐laden hydrogel yarns are collected on a rotating drum using a novel wet spinning strategy. Cells encapsulated into the hydrogel fibers elongate in the direction of the fiber axis, unraveling the potential of the proposed platform for tendon tissue engineering.